Clinical and sociodemographic profile of acute intoxications in an emergency department: A retrospective cross-sectional study - Aguilón-Leiva, Juan José; Tejada-Garrido, Clara Isabel; Echániz-Serrano, Emmanuel; Mir-Ramos, Eduardo; Torres-Pérez, Antonio Manuel; Lafuente-Jiménez, Alberto; Martínez-Soriano, María; Santolalla-Arnedo, Iván; Czapla, Michal; Smereka, Jacek; Juárez-Vela, Raúl; Satústegui-Dordá, Pedro José (Frontiers in Public Health, 2022)
Background Epidemiological studies about acute poisoning are useful for developing clinical toxicology, especially those carried out in hospital emergency departments. We aimed to evaluate acute intoxication clinical and sociodemographic profile in South Aragon Hospital, Spain. Methods We carried out a retrospective cross-sectional study. We included 442 patients treated for acute poisoning in the emergency department during the 3 years 2015–2018. In the inferential analysis, the Chi-square test was used to compare proportions, and the Mann-Whitney U-test was used to compare ranges. A confidence level of 95 per cent was considered in all tests. Results The mean age was 44.1 years. 57.2% were men. Drugs of abuse were present in 243 patients (55%), drugs in 172 (38.9%), chemicals in 57 (12.9%) and three patients (0.7%) were poisoned by mushrooms. Nine different drugs of abuse, 73 drugs, 15 chemical compounds and 2 varieties of mushrooms were registered. Of the intoxicated patients, 92.3% had symptoms, 84.2% received treatment and 78.7% were discharged from the emergency department. Conclusions We obtain a clear clinical and sociodemographic profile of intoxicated patients who come to the emergency department; the five toxins that cause most acute poisoning are: alcohol, benzodiazepines, antiarrhythmics, cannabis and carbon monoxide.